A Coordination Strategy between PV Generators and Storages based on Droop Control in AC Microgrids. Issue 1 (April 2020) - Wang, Liang; Wei, Wei; Xia, Yanghong
Abstract: In an islanded AC microgrid, the coordination strategy between generations and storages is often designed to ensure the stability and economy of the system. In this article, for an AC microgrid dominated by photovoltaic (PV) generators, a strategy based on droop control is proposed to realize the generation-storage coordination. PV generators change their active and reactive power output by catching the changes in bus frequency and voltage, which can prevent storages from over-charged and make the bus voltage more stable. Storages are controlled by a droop algorithm based on state-of-charges (SOCs) to achieve SOCs balance among multiple storages. When the SOCs are too low, secondary loads (SLs) will be removed through a loads management, and the rest primary loads (PLs) will be powered entirely by PVs, which can prevent storages from over-discharged. Simulation based on Matlab successfully verifies the proposed coordination strategy.